Genome-wide association study of nevirapine hypersensitivity in a sub-Saharan African HIV-infected population. (5th January 2017) - Carr, Daniel F.; Bourgeois, Stephane; Chaponda, Mas; Takeshita, Louise Y.; Morris, Andrew P.; Castro, Elena M. Cornejo; Alfirevic, Ana; Jones, Andrew R.; Rigden, Daniel J.; Haldenby, Sam; Khoo, Saye; Lalloo, David G.; et al.
Abstract : Background: The antiretroviral nevirapine is associated with hypersensitivity reactions in 6%–10% of patients, including hepatotoxicity, maculopapular exanthema, Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). Objectives: To undertake a genome-wide association study (GWAS) to identify genetic predisposing factors for the different clinical phenotypes associated with nevirapine hypersensitivity. Methods: A GWAS was undertaken in a discovery cohort of 151 nevirapine-hypersensitive and 182 tolerant, HIV-infected Malawian adults. Replication of signals was determined in a cohort of 116 cases and 68 controls obtained from Malawi, Uganda and Mozambique. Interaction with ERAP genes was determined in patients positive for HLA-C*04:01 . In silico docking studies were also performed for HLA-C*04:01 . Results: Fifteen SNPs demonstrated nominal significance ( P < 1 × 10 −5 ) with one or more of the hypersensitivity phenotypes. The most promising signal was seen in SJS/TEN, where rs5010528 ( HLA-C locus) approached genome-wide significance ( P < 8.5 × 10 −8 ) and was below HLA -wide significance ( P < 2.5 × 10 −4 ) in the meta-analysis of discovery and replication cohorts [OR 4.84 (95% CI 2.71–8.61)]. rs5010528 is a strong proxy for HLA-C*04:01 carriage: in silico docking showed that two residues (33 and 123) in the B pocket were the most likely nevirapine interactors. There was no interaction between HLA-C*04:01 and ERAP1, but there is a potential protective effect with ERAP2 [ P = 0.019, OR 0.43 (95% CI 0.21–0.87)]. Conclusions: HLA-C*04:01 predisposes to nevirapine-induced SJS/TEN in sub-Saharan Africans, but not to other hypersensitivity phenotypes. This is likely to be mediated via binding to the B pocket of the HLA-C peptide. Whether this risk is modulated by ERAP2 variants requires further study.